Efektivitas Penerimaan Pajak Bumi Dan Bangunan (PBB) Di Lembang Pemanukan Kecamatan Gandangbatu Sillanan Kabupaten Tana Toraja - Tangkeallo, Dian Intan; Kannapadang, Dwibin (Jurnal Ekonomi, Bisnis dan Terapan (JESIT), 2021)
This study aims to determine the effectiveness of land and building tax revenue (PBB) in Lembang Pemanukan, Gandangbatu Sillanan District, Tana Toraja Regency. The type of research used is descriptive quantitative where the researcher provides an overview of how the level of effectiveness of land and building tax revenue (PBB) in Lembang Pemanukan. The data analysis technique used in this research is effectiveness, namely comparing the realization of PBB revenue with the target of PBB revenue. The results showed that the collection of land and building taxes in Lembang Pemanukan, Gandangbatu Sillanan district, Tana Toraja Regency from 2018-2020 was in the effective or successful category. The effectiveness of land and building tax receipts in Lembang Pemanukan, Gandangbatu Sillanan sub-district in 2018-2020 was caused by several things, including public awareness in paying PBB, socialization of taxes to the public directly, so that the PBB reached the target which was said to be effective because it almost reached the PBB target.